Study of the Mechanical Behavior of Radially Grown Fivefold Twinned Nanowires on the Atomic Scale. Issue 26 (27th May 2016) - Yue, Yonghai; Zhang, Qi; Yang, Zhenyu; Gong, Qihua; Guo, Lin
Abstract : In situ bending tests and dynamic modeling simulations are for the first time revealing the mechanical behavior of copper nanowires (NW) with radially grown fivefold twin structures on the atomic scale. Combining the simulations with the experimental results it is shown that both the twin boundaries (TBs) and the twin center act as dislocation sources. TB migration and L‐locks are readily observed in these types of radially grown fivefold‐twin structures.